beta-TCP/HA with or without enamel matrix proteins for maxillary sinus floor augmentation: a histomorphometric analysis of human biopsies - Nery, James Carlos (2017)
Background: It is still unclear whether enamel matrix proteins (EMD) as adjunct to bone grafting enhance bone healing. This study compared histomorphometrically maxillary sinus floor augmentation (MSFA) with beta-TCP/HA in combination with or without EMD in humans. Methods: In ten systemically healthy patients needing bilateral MSFA, one side was randomly treated using beta-TCP/HA mixed with EMD (BC + EMD) and the other side using only beta-TCP/HA (BC). After 6 months, biopsies were harvested from grafted areas during implant installation, being histologically and histomorphometrically analyzed. Differences between the groups considering new bone formation, soft tissues, and remaining BC were statistically evaluated. Results: All patients showed uneventful healing after MSFA, and dental implant installation was possible in all patients after 6 months. Histological analysis showed newly formed bone that was primarily woven in nature; it was organized in thin trabeculae, and it was occasionally in contact with residual bone substitute particles, which appeared in various forms and sizes and in advanced stage of degradation. Mean bone area was 43.4% (CI95 38.9; 47.8) for the BC group and 43.0% (CI95 36.6; 49.5) for the BC + EMD group. Mean soft tissue area was 21.3% (CI95 16.5; 26.2) for BC group and 21.5% (CI95 17.7; 25.3) for BC + EMD group, while the remaining biomaterial was 35.3% (CI95 36.6; 49.5) and 35.5% (CI95 29.6; 41.3) for BC and BC + EMD group, respectively. Conclusions: MSFA with BC resulted in adequate amounts of new bone formation allowing successful implant installation; adding EMD did not have a significant effect.